Manajemen Mutu Sekolah Melalui Pengembangan Profesional Guru di Sekolah Dasar Negeri - Lukman Nasution; Seila Rizkina; Ivan Kurnia Ndruru; Namira Georgina Sinuhaji (Journal of Islamic Education Students (JIES), 2025)
This study aims to examine: (1) how schools plan development based on needs (need assessment), (2) how development is implemented (forms, mechanisms, actors, and resources), (3) how impact evaluation is conducted (indicators, evidence of changes in practice, and feedback), and (4) how follow-up to continuous improvement is realized. This research method uses a descriptive qualitative approach. Descriptive qualitative examines school quality management through teacher professional development at a public elementary school in Gido District. It focuses on planning, implementation, evaluation, and follow-up. Data were collected through interviews, observation, documentation, and interactive analysis, with validity guaranteed by triangulation and member checking. Informants were selected purposively over three to six months of research. Based on the research results,: (1)Teacher professional development planning In Gido District Public Elementary School, it has been implemented as part of school quality management, but it is not yet fully based on systematic and data-based needs assessment. (2) The implementation of teacher professional development is generally carried out through KKG activities as a collaborative learning vehicle. (3) Evaluation of the impact of teacher professional development has not been carried out optimally because it is still informal and does not use structured indicators. (4) Follow-up on teacher professional development has not been systematically integrated into the school's internal quality assurance.